The stolen hours - Eskens, Allen, 1963- (New York : Mulholland Books, Little, Brown and Company, 2021)
"Lila Nash is on the verge of landing her dream job--working as a prosecutor under the Hennepin County Attorney--and has settled into a happy life with her boyfriend, Joe Talbert. But when a woman is pulled from the Mississippi River, barely alive, things in the office take a personal turn"--
Keywords: Public prosecutors -- Fiction; Criminal investigation -- Fiction; Victims of violent crimes -- Fiction; Minnesota -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Novels